2008
DOI: 10.1007/978-3-540-74004-9_13
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Usefulness of Artificial Herbivory in Plant-Herbivore Studies

Abstract: Artificial damage is a popular method in plant-herbivore studies, because the use of real herbivores is often laborious and because it may be virtually impossible to use herbivores in many experimental setups. We made a literature search of studies that tested whether natural and artificial damage have similar effects on plants. Of 46 studies found, 33 (72 %) reported a significant difference between responses to artificial and natural herbivore damage in at least one of the statistical tests included. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…Because we standardized the total damage, we assume that variation in the amount of insect damage among plants had a negligible contribution to variation in tolerance. According to a review, the effects of natural and artificial damage on tolerance are fairly similar (Lehtilä and Boalt 2004). To mimic natural growth environment, the potted plants were transferred to a semi-forested enclosure after herbivore damage treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Because we standardized the total damage, we assume that variation in the amount of insect damage among plants had a negligible contribution to variation in tolerance. According to a review, the effects of natural and artificial damage on tolerance are fairly similar (Lehtilä and Boalt 2004). To mimic natural growth environment, the potted plants were transferred to a semi-forested enclosure after herbivore damage treatment.…”
Section: Methodsmentioning
confidence: 99%
“…No defoliation theses showed any significant differences compared to the undefoliated ones. Despite several studies simulated herbivory effects on plants using mechanical defoliation or included mechanically defoliated control plants, this approach is deemed appropriate when studying simple biotic interactions, but not necessarily for complex interactions including different trophic levels (Hjältén 2004, Lehtilä & Boalt 2004, as the ones investigated. Although most of the papers published on AM symbiosis report open field experiments, pot experiments in semi-controlled conditions, like those performed in this work, have allowed to study some of the mechanisms involved in plant-AM fungi interaction under defoliation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In natural conditions, I. purpurea individuals can be exposed to snail damage (personal observation) or volatile emissions from neighbor plants and the induced twining could help reduce further damage to apical portions of the plant (Gianoli & Molina-Montenegro 2005, Atala & Gianoli 2008. It has been suggested that natural damage is qualitatively and quantitatively different from artifi cial damage , Lehtilä & Boalt 2004. Results show that artifi cial and natural damage can induce twining in I. purpurea, giving the response an ecological relevance that could impact natural populations, reducing further leaf damage and, therefore, increasing fi tness in the presence of herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…Artifi cial damage to the leaves and chemical induction under controlled conditions are useful tools for assessing induced responses. However, the application of natural damage (e.g., exposition to herbivores) could be more relevant to understanding the twining in an ecological context , Lehtilä & Boalt 2004.…”
Section: Introductionmentioning
confidence: 99%